Answer:
√7x−49√x
Explanation:
First of all, expand by multiplying √7x⋅√x and √7x⋅7√7respectively:
√7x(√x−7√7)=√7x⋅√x−√7x⋅7√7
... you can express √7x as √7⋅√x...
=√7⋅√x⋅√x−√7⋅√x⋅7⋅√7
=√7⋅(√x)2−(√7)2⋅√x⋅7
... the operations squaring and taking the square root "eliminate each other"...
=√7⋅x−7⋅√x⋅7
=√7x−49√x
Hope that this helped!
Answer:
Step-by-step explanation:
Isolate the term of n from one side of the equation.
<h3>n-1/8=3/8</h3>
<u>First, add by 1/8 from both sides.</u>
n-1/8+1/8=3/8+1/8
<u>Solve.</u>
<u>Add the numbers from left to right.</u>
3/8+1/8=4/8
<u>Common factor of 4.</u>
4/4=1
8/4=2
<u>Rewrite as a fraction.</u>
=1/2
n=1/2
<u>Divide is another option.</u>
1/2=0.5
n=1/2=0.5
- <u>Therefore, the final answer is n=1/2=0.5.</u>
I hope this helps you! Let me know if my answer is wrong or not.
Y=1000*1.03^x is the correct compound recursive formula!
In order to evaluate the given function at x = -3, simply replace "x" in the function with -3 and solve.
<em>Multiply -4 and -3 in the function above.</em>
<em>Add 3 on both sides of the equation.</em>
<em>Add 2y on both sides of the equation.</em>
<em>Divide both sides of the equation by -3.</em>
Therefore, at x = -3, the value of y = -5. Hence, f(-3) = -5.
Answer:
f(-3) = -5
<em />
Answer:
x = 8
Step-by-step explanation:
0.4x - 1.2 = 0.15x + 0.8
0.4x - 1.2 + 1.2 = 0.4x
0.15x + 0.8 + 1.2 = 0.15x + 2
0.4x = 0.15x + 2
0.4x - 0.15x = 0.25x
0.15x + 2 - 0.15x = 2
0.25x = 2
0.25x / 0.25 = x
2 / 0.25 = 8
x = 8